(untitled) (Academia Journal of Medicine, 2025)
Background: Dental caries remains a prevalent chronic disease in children, influenced by diet, microbial activity, and oral hygiene. Milk is a widely consumed beverage with both protective and cariogenic potential, depending on its composition and sugar content. This study evaluated the cariogenic effects of natural and flavoured milk beverages on primary teeth using an in vitro Streptococcus mutans biofilm model. Materials and Methods: Sixty caries-free primary teeth were sectioned into enamel slabs and randomly allocated into six groups: cow, buffalo, goat, strawberry-flavoured, vanilla flavoured milk, and saline control (n=10 each). Enamel slabs were inoculated with S. mutans and exposed to the respective beverages three times daily for three days. Baseline and post exposure surface microhardness were measured using the Brinell hardness test. Percentage surface hardness loss was calculated, and data were analyzed using one-way ANOVA with Tukey’s post hoc test and paired t-tests (p0.05). Natural milk types (cow, buffalo, goat) caused moderate enamel demineralization, whereas flavoured milk beverages led to significantly higher microhardness loss (p